SEDIMENTATION RATES AND CALCAREOUS NANNOFOSSIL BIOSTRATIGRAPHY OF THE NANGGULAN FORMATION, KULON PROGO, INDONESIA - Resti Samyati Jatiningrum; Rivdhal Saputra; Gaudensia Phang; Tokiyuki Sato (Marine Geological Institute of Indonesia, 2022)
The Nanggulan Formation is the oldest sedimentary rock of Paleogene age that was deposited in the eastern part of the Southern Central Java Basin. A total of 103 nannofossil samples were taken from two traverses in the study area, i.e., the Watupuru and Jetis Routes. Based on the biodatum identified from the nannofossil samples, the biostratigraphy of the rock formation is divided into five zonations, namely the upper part of Zone NP16, Zone NP17, the lower part of Zone NP18, the upper part of Zone NP22, and the lower part of Zone NP23, expanding from 41.1 Ma to 32.2 Ma of age (Middle Eocene to Early Oligocene). Only Zone NP17 is identified as a complete zone, whereas the other four are observed as partial. The fluctuation of global sea level is believed to be an influence on the deposition of the Nanggulan Formation. The sedimentation rate and the change of nannofossil species shows a decrease of oligotrophic (Sphenolithus) and an increase of eutrophic (Reticulofenestra) taxa, especially in small reticulofenestrids (Reticulofenestra spp.). This occurrence suggests a shift in the environmental conditions from an oligotrophic condition around 41.1 Ma to a eutrophic one, particularly after 40.40 Ma. The enhanced eutrophication in the Watupuru and Jetis Routes was caused by an increasing terrigenous input in 40.40 Ma and after, consequently providing nutrient availability on the water surface. This interpretation is supported by the increase in the sedimentation rate when sea level slightly decreased in 40.40 Ma.